WATERS TOWARDS RICE TRADE FLOW IN 14TH CENTURY OF JAVA - Riza Afita Surya; Rif'atul Fikriya (Universitas Negeri Malang, 2020)
Waters as rain, rivers, and seas are one the most common feature found upon Southeast Asian region. It has been establishing this region significantly distinctive along with others. Water is such profound thing everywhere, but it helds most importantly in Southeast Asia Maritime region, with its long shorelines in relation to it landmass, and with the enormous expanses of surrounding Island of Southeast Asia and abutting the shores of Mainland Southeast Asia. Waters in form such rain, rivers, and seas undoubtly giving a certain pattern of social and economical circumstance towards society. Java was known as the biggest rice producer until 19th century, especially manufactured among Javanese kingdoms. Rice had been the trademark of exchange in Java that was contributed across the land overtime. Here, wet rice cultivation has been a typical technique engaged in Java and remains until presents. This article discusses the water impact towards rice trade in Java during 14th century.